Integrated Transcriptomic Analysis of the miRNA–mRNA Interaction Network in Thin Endometrium - Zong, Lu; Zheng, Shengxia; Meng, Ye; Tang, Wenjuan; Li, Daojing; Wang, Zhenyun; Tong, Xianhong; Xu, Bo (Frontiers in Genetics, 2021)
Although the thin endometrium (TE) has been widely recognized as a critical factor in implantation failure, the contribution of miRNA-mRNA regulatory network to the development of disease aetiology remains to be further elucidated. This study performed an integrative analysis of the miRNA-mRNA expression profiles in the thin and adjacent normal endometrium of 8 patients with intrauterine adhesion to construct the transcriptomic regulatory networks. A total of 1093 differentially expressed genes (DEGs) and 72 differentially expressed miRNAs (DEMs) were identified in the thin adhesive endometrium of the TE group compared with the control adjacent normal endometrial cells. Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway analyses showed that DEGs and the target genes of DEM were significantly enriched in angiogenesis, cell growth regulation and Wnt signalling pathway. Multiple hub genes (CAV1, MET, MAL2, has-mir-138, ARHGAP6, CLIC4, RRAS, AGFG1, has-mir-200, and has-mir-429) were identified by constructing the miRNA-mRNA regulatory networks. Furthermore, a miRNA-mRNA-pathway-function analysis was conducted, and the hub genes were enriched in the FoxO signalling pathway, cell growth regulation, inflammatory response regulation and regulation of autophagy pathways. Our study is the first to perform integrated mRNA-seq and miRNA-seq analyses in the thin adhesive endometrium and the control adjacent normal endometrial cells. This study provides new insights into the molecular mechanisms underlying the formation of thin endometrium.